Dismenore Primer dan Faktor Gizi yang Mempengaruhi - Ade Dewi Oktaviani; Zulfiana Dewi (POLTEKKES KEMENKES MANADO, 2021)
Background : The prevalence of dysmenorrhea in Indonesia is 64.25% which consists of 54.89% of primary dysmenorrhea. Dysmenorrhea greatly affects adolescents age of school because it causes disruption of daily activities. According to information from the UKS watchman the data obtainable during January - August 2019 were found to be 5.9% with complaints of dysmenorrhea at various of pain levels.. Objectives : This research was to knowing the correlation between menstruation duration, fast food consumption and physical activity with primary dysmenorrhea in female students. Methods: This type of research is analytic observational using cross sectional design.The research sample was part of class X and XI students taken by purposive sampling with inclusion and exclusion criteria. The variables studied were primary dysmenorrhea, menstruation duration, fast food consumption and physical activity. Data collection using google form. Data analysis using Rank Spearman correlation test. Results: The students experienced primary dysmenorrhea with a grade 1 of 39.3% and the lowest grade 3 of 6%, normal menstrual duration of 53.6%, often fast food consumption of 63.1%, mostly moderate physical activity. Conclusions: There is a correlation between menstrual periods, fast food consumption and physical activity with primary dysmenorrhea.